High‐resolution X‐ray crystal structure of bovine H‐protein using the high‐pressure cryocooling method. (6th October 2013) - Higashiura, Akifumi; Ohta, Kazunori; Masaki, Mika; Sato, Masaru; Inaka, Koji; Tanaka, Hiroaki; Nakagawa, Atsushi
<x xml:space="preserve">Abstract</x> Recently, many technical improvements in macromolecular X‐ray crystallography have increased the number of structures deposited in the Protein Data Bank and improved the resolution limit of protein structures. Almost all high‐resolution structures have been determined using a synchrotron radiation source in conjunction with cryocooling techniques, which are required in order to minimize radiation damage. However, optimization of cryoprotectant conditions is a time‐consuming and difficult step. To overcome this problem, the high‐pressure cryocooling method was developed (Kim et al., 2005) and successfully applied to many protein‐structure analyses. In this report, using the high‐pressure cryocooling method, the X‐ray crystal structure of bovine H‐protein was determined at 0.86 Å resolution. Structural comparisons between high‐ and ambient‐pressure cryocooled crystals at ultra‐high resolution illustrate the versatility of this technique. This is the first ultra‐high‐resolution X‐ray structure obtained using the high‐pressure cryocooling method.